Health related quality of life in children following Fontan surgery: A Malaysian perspective - Leong, Ming Chern; Mohamed, Mohamed Ajmal Haj; Basran, Nurul Fazira; Azeman, Nor Athirah (Elsevier Ireland, 2024)
Background: Children with Fontan circulation suffer from morbidities and physical limitations that affect their quality of life. The study examined the health-related quality of life (HRQoL) of children in Malaysia following the Fontan procedure. Methods: All patients who are 8 years and older and who had undergone Fontan palliation for at least 1 year were assessed using electronically distributed, aged-based Pediatric Quality of Life Inventory™ (PedsQL) Generic and Cardiac modules. The scores from the patients were compared with those of aged-match students in the Klang Valley and patient's parents. Results: A total of 133 patients [time after Fontan: 6.24 years (IQR: 2.54, 8.54); SpO2: 92 % (IQR: 88, 95)] and parents and 130 normal subjects participated in the study. Fontan patients have reduced HRQOL scores compared to their healthy peers in almost all domains. Patients with NYHA class I demonstrated higher PedsQL scores in almost all domains. Patients with SpO2 < 95 % and taking more medication had lower PedsQL scores in total and physical score. Similarly, those with many complications show significantly low PedsQL scores in all domains. There was poor agreement between patients' and parents' perceived HRQoL in most of the domains in the generic module, but the difference was not as explicit in the cardiac module. Conclusions: Fontan patients had a lower perceived quality of life compared to healthy controls. Physical ability and Fontan complications influenced the perceived quality of life, especially in younger children. Parents generally underestimate the impact of Fontan towards their children's quality of life. © 2024 Elsevier B.V.